PENERAPAN CITIZEN LAWSUIT TERHADAP SKEMA GUGATAN OBJEK GUGATAN KEBIJAKAN KEMENTERIAN PANRB TERKAIT TENAGA HONORER DALAM LINGKUP PERADILAN TATA USAHA NEGARA - Adzra Arvianda; Annastasya Divana P M; Hanuun Zainum A; Santi Hapsari Dewi Adikancana (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2022)
Law No. 5 of 2014 regulates the legality of Honorary Personnel as non-ASN employees. In essence, there are provisions regarding the appointment of honorary personnel to become civil servants with conditions that must be met. Moreover, the problem continues when the number of Honorary Personnel in Government Agencies increases and disrupts the balance of the arrangement of human resources (HR) of the apparatus in each of these agencies. As a settlement effort, the PANRB Ministry issued the PANRB Ministerial Letter Number B/185/M.SM.02.03/202 which emphasized the provisions of PP. 49 of 2018. This becomes an interesting topic when it is associated with the issue of the rights of Honorary Personnel and the application of the Citizen Lawsuit lawsuit to the Administrative Court. This writing uses a normative research method with a literature study which is then analyzed qualitatively and conclusions are drawn using the inductive method. The conclusion that was found was that the Honorary Personnel had the right to file a lawsuit with the Administrative Court because the object of the disputed letter included the State Administrative Court. However, Citizen Lawsuit is not optimal enough as a scheme for filing a lawsuit and it is better to use ordinary legal practices. Keywords : citizen lawsuit, state administrative courts, honorary staff